Surgical Site Infections after Laparoscopic Bariatric Surgery: Is Routine Antibiotic Prophylaxis Required? - Aktas, Aydin; Kayaalp, Cuneyt; Gunes, Orgun; Kirkil, Cuneyt; Tardu, Ali; Aydin, Mehmet Can; Aygen, Erhan (Mary Ann Liebert, Inc, 2021)
Background: It is a challenging question, especially in bariatric surgery (BS), whether antibiotic prophylaxis is necessary in all cases; considering the serious consequences of surgical site infection (SSI) on the one hand and irrational use of antibiotics on the other. The aim of this study was to determine the need/rationale for antibiotic prophylaxis in patients undergoing laparoscopic bariatric surgery, especially low-risk patients. Methods: This retrospective analysis involved 313 morbidly obese patients (body Mass Index [BMI] >= 40) who underwent laparoscopic BS at three medical centers between September 2018 and June 2019. During the trial, no inducement was given to use antibiotics, and the centers had chosen whether to use prophylaxis. The U.S. Centers for Disease Control and Prevention (CDC)-2016 criteria were used for the diagnosis of SSI. Results: Antibiotic prophylaxis was given to 181 patients, and the SSI rate in the entire series was 4.5% (14/313). There was no significant difference in SSI between the group who received antibiotics and that who did not (2.8% versus 6.8%, respectively; p = 0.09). Post-operative intra-abdominal complications were the main independent determinant for SSIs (p < 0.001). Antibiotic prophylaxis did not have any significant effect on the rate of SSI caused by these complications (2.2% versus 3.8%, respectively; p = 0.50). The second independent factor was the rate of SSI in patients with super-obesity (BMI >= 60), particularly incisional SSIs (p < 0.001). Antibiotic prophylaxis did not produce any significant decrease in the rate of SSI in patients with a BMI < 60 (2.8% versus 5.5%, respectively; p = 0.24). When these two independent factors were excluded, there were no patients with SSI in the no-antibiotics group, and only one in the antibiotic prophylaxis group (0.5%) (p = 1.00). Conclusions: Routine antibiotic prophylaxis should be questioned in laparoscopic BS. Prophylaxis may reduce incisional SSI in patients with a BMI of >= 60. In other cases, antibiotic prophylaxis does not provide a decrease in SSI
Keywords: antibiotic prophylaxis; morbid obesity; one-anastomosis gastric bypass; Roux-en-Y gastric bypass; sleeve gastrectomy